Expression of alloantigens LY-5 and LY-6 on cytotoxic effector cells. - Woody, J; Feldmann, M; Beverley, P; McKenzie, I (1977)
With anti-Ly antisera and complement it has been possible to demonstrate that cytotoxic effector cells generated in vitro against allogeneic cells carry the alloantigen Ly-5 and Ly-6. The studies show that antisera directed against the Ly-6 antigens, together with complement, eliminate essentially all of the killer cells, of the appropriate strain, while killing only 50 to 60% of Thy-1+ cells. Anti-Ly-5 antsera and complement lysed 55 to 65% of Thy-1+ cells and killed a significant portion, but not all, of the cytotoxic cells. The later finding was investigated in more detail since it suggested a degree of heterogeneity within the killer cell subpopulation. However, the data did not support that conclusion, at least for allogeneic killer cells.